Female Condition in the Chilean Feminist Student Movement of 2018 [la Condición Femenina en el Movimiento Estudiantil Feminista Chileno del Año 20181 - Rubio-Manriquez, M; Franulic-Depix, A (Universidad de la Serena,Departamento de Artes y Letras, 2023)
The purpose of this article is to establish the characteristics of the female condition underlying in the meaning of being a woman from a female group of college students’ discourse which participated in the chilean feminist student movement of 2018. This characterization is made from the feminist analysis of discourse based on the sexual difference thought and uses the concept of ideologeme proposed by Kerbrat-Orecchioni (1983). The methodology used is a qualitative study oriented to explain the meaning of being a woman in the discourse expressed by 14 students, all of whom a semi-structured interview was applied to. The results indicate that the female condition is expressed in the ideologemes of the idea of equality between men and women and in what is represented by identity politics (Sartori, 1996). In conclusion, the gender theory that young female students have access to when expressing their freedom contradictorily denies it because it replaces the feminine sexual difference, free of stereotypes, with the female condition that, from a discourse that appears to be progressive, can be abolished by equating women to men or multiplying gender identities. © The Author(s) 2023.